2013
DOI: 10.2118/166142-pa
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Arising From Well-Construction Failure—Differences Between Barrier and Well Failure, and Estimates of Failure Frequency Across Common Well Types, Locations, and Well Age

Abstract: Summary Do oil and gas wells leak to the environment? This paper will show the great majority of wells do not pollute. The purpose of this paper is to explain basic concepts of well construction and illustrate differences between single-barrier failure in multiple-barrier well design and outright well-integrity failure that could lead to pollution by use of published investigations and reviews from data sets of more than 600,000 wells worldwide. For US wells, while individual-barrier failures (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 56 publications
4
37
0
Order By: Relevance
“…The majority (89%) of horizontal wells also have production casings that are either fully cemented or cemented above the shallowest hydrocarbonbearing formation (20). This evidence supports the growing consensus that wellbore barrier failure, not the process of high-volume hydraulic fracturing itself, is the main thermogenic stray gas migration pathway (1,3,9,10,20,27,29,30).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The majority (89%) of horizontal wells also have production casings that are either fully cemented or cemented above the shallowest hydrocarbonbearing formation (20). This evidence supports the growing consensus that wellbore barrier failure, not the process of high-volume hydraulic fracturing itself, is the main thermogenic stray gas migration pathway (1,3,9,10,20,27,29,30).…”
Section: Resultssupporting
confidence: 62%
“…These rates are 1.6-4 times lower than the fraction of shale gas wells in Pennsylvania that have led to methane migration into groundwater (0.24%) (9). The contrast in rates highlights differences in geology, regulations, operators, and construction practices among different petroleum-producing basins (29)(30)(31). It should also be noted that the occurrence of thermogenic stray gas is likely underrepresented because of the spatial density of sampled water, willingness of landowners to have their water tested, and the possibility that stray hydrocarbons are rapidly oxidized under certain redox conditions (38).…”
Section: Resultsmentioning
confidence: 96%
“…Well integrity to prevent leaks of gas and other fluids to groundwater or to ground surface is a cornerstone of environmental protection in all oil and gas drilling operations. Well integrity can be compromised as a result of poor completion or abandonment, formation damage around the wellbore, geomechanical effects, geochemical degradation of well cements, casing and tubing corrosion, and casing failure as a result of thermal or mechanical stresses (see King and King [2013] for a review). Poor well construction is a critical issue throughout the oil and gas industry and is not unique to any specific region, type of well, drilling period or sector of activity.…”
Section: Water Resources Researchmentioning
confidence: 99%
“…Oil and gas wells are constructed with multiple engineered barriers against fluid flow leakage into other aquifers, protected groundwater, and/or atmosphere [19]. Local loss of well integrity may occur when there is debonding of cement from casing or from the rock wall, when the well cement has wormholes or fractures, when the well cement is not properly set in the well annulus, or when the casing fails due to stress [10].…”
Section: Introductionmentioning
confidence: 99%
“…In all these cases, leakage of reservoir or formation fluids, inside or outside well casing, will be stopped by the next barrier (e.g., the next cement plug or the next well section with good quality cement). However, if a continuous leakage pathway is formed, then the well loses its integrity and fails as a whole [19]. In a study of more than 300,000 wells in Alberta, Bachu & Watson [20], have found that approximately 6.5% of the oil and gas wells in the province have lost their integrity, leading to surface casing vent flow or gas migration.…”
Section: Introductionmentioning
confidence: 99%